Case report: Distinct neurologic manifestation and cytokine profile of a child with COVID-19-associated acute fulminant encephalitis - Chang, Yu-Ming; Chen, Cheng-Han; Wang, Jieh-Neng; Cheng, Chao-Min; Tu, Yi-Fang; Shen, Ching-Fen (Frontiers in Medicine, 2023)
The neurologic manifestations of coronavirus disease 2019 (COVID-19) may range from mild symptoms such as headache or confusion to profound encephalopathy with variable outcomes and sequelae. Here, we reported a case of fatal COVID-19-associated encephalitis with acute fulminant cerebral edema, presenting first with visual hallucination and then a rapid progression into comatose status in a few hours. Serial brain computed tomography depicted cerebral edematous changes from bilateral ventral temporal lobe to the whole brain leading to brain herniation. Multiple cytokines in serum and cerebrospinal fluid (CSF) were increased, with a more prominent rise in the CSF. Therefore, we postulated a hypothesis regarding the mechanism of this fulminant encephalitis that the SARS-CoV-2 virus attacked ventral temporal lobes initially, triggered a severe cytokine storm, and then led to subsequent disruption of the blood-brain barrier, diffuse brain edema, and brain herniation. The trend of cytokine profiles over time may aid in diagnosing and evaluating the severity and prognosis of COVID-19-associated encephalitis.